Characterisation of SNPs associated with growth rate in dusky kob (Argyrosomus japonicus), using exome sequencing - Jackson, Tassin Kim (Stellenbosch : Stellenbosch University, 2020)
Thesis (MScAgric)--Stellenbosch University, 2020.